Development of A Documentary Video of Kusmindari Triwati as a Dance Figure of Pontianak City for Students - Oktariani, Dwi; Djau, Nurmila Sari (Gorga : Jurnal Seni Rupa, 2025)
The aim of this research is to make a documentary video of a dance figure in Pontianak City, namely Kusmindari Triwati. The importance of documentation in the artistic work of a dance figure can be an inspiration for artists, arts and culture teachers, the government and the community to get to know more about the figure of the traditional dance art preserver and its developments in the form of new creations in Pontianak City until they spread to the national and international levels. The development of documentary video media makes this research use an R&D approach, which is explained in qualitative descriptive words. The results of research and development show that the documentary video of Kusmindari Triwati as a dance figure in Pontianak City is in good criteria. . The documentary video contains a biography of Kusmindari Triwati which tells the story of her accomplishments and long journey as a dance figure, packaged in the form of an expository video where there are several figures who directly convey what happened in the field through interviews shown in this video. Data collection techniques were carried out by means of observation, interviews, literature studies, questionnaires and documentation. The results obtained based on material expert validation, media expert tests, and audience response tests can be categorized as very good and worthy of being disseminated to the wider community.